Identifying the leading sector in the Iraqi economy through the interrelationships between sectors - applied research - cheid, Fareq; salih, Mohamed (Journal of Economics and Administrative Sciences, 2021)
Analyzing the size of the interrelationships between the main economic sectors in the Iraqi economy is an important necessity to know the impact of each sector on other economic sectors on the basis of the interrelationships and reciprocity between them, and what these relationships have achieved in terms of enhancing development and increasing the gross domestic product. To achieve the objectives of the study, we relied on mathematical (quantitative) analysis using user-product tables. Issued by the Ministry of Planning / Central Bureau of Statistics and Research (Directorate of National Accounts) for the economic sectors that make up the Iraqi economy. The study concluded that there are weak interdependence relations between economic sectors, which indicates the weak contribution of these sectors in creating the gross domestic product and the tendency of the Iraqi economy towards structural disintegration and dependence on exports from outside the country and deepening the phenomenon of a rentier economy. Likewise, the electricity, gas and water sector is the leading sector and one of the sectors most interconnected with the rest of the sectors, and accordingly the study recommended the necessity of strengthening interdependence relations between it and the economic sectors by adopting an industrialization strategy that works on a package of economic reform programs and restructuring the components of the gross domestic product. And giving a role in deepening development processes and strengthening networking